Diversity of eukaryote plankton and phycotoxins along the West Kalaallit Nunaat (Greenland) coast - Rodríguez-Marconi, Susana; Krock, Bernd; Tillmann, Urban; Tillmann, Anette; Voss, Daniela; Zielinski, Oliver; Vásquez, Mónica; Trefault, Nicole (Frontiers in Marine Science, 2024)
The West Kallaallit Nunaat (Greenland) coast, characterized by a variety of fjords, bays, and channels influenced by glacier melting and Atlantic and Arctic waters, is one of the most affected ecosystems by climate change. Here, we combine oceanography, optics, microscopy, high throughput sequencing, microalgal strain establishments, and state-of-the-art analytical methods to fully characterize the diversity, community composition, and toxin repertoire of the eukaryotic plankton members of the coast of the West Kalaallit Nunaat (Greenland). Results indicate that the West Kalaallit Nunaat (Greenland) coast is a complex and oceanographically challenging system, where the superimposition of water masses of different origins, the penetration of light and its repercussions, generate mainly vertical, rather than horizontal heterogeneity in nutrient concentration and plankton biomass. Nevertheless, our molecular data reveal a strong homogeneity and a high diversity in the plankton community along the Greenland coast. We confirmed the presence of five phycotoxin groups: domoic acid and paralytic shellfish toxins were most abundant along the transect from Qeqertarsuup Tunua (Disko Bay) to the northern Baffin Bay, while spirolides, yessotoxins and pectenotoxins were predominant in Nuup Kangerlua (GodthaabFjord) and Qeqertarsuup Tunua (Disko Bay). Concentrations of these phycotoxins correlate differently to temperature, salinity and nutrients, reflecting the ecological differences of their producers. Patterns of paralytic shellfish and spirolide toxins suggest the presence of genetically distinct populations of Alexandrium along the Western Kalaallit Nunaat (Greenland). Phytoplankton strains isolated during this oceanographic campaign resemble, in most cases, the toxin profiles of the respective field stations. Overall, this work shows the diversity and community composition of the plankton at the Western Kalaallit Nunaat coast and reveals a distinct spatial distribution of phycotoxins, with certain toxin groups restricted to specific areas.